The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4186/ej.2015.19.4.117
|View full text |Cite
|
Sign up to set email alerts
|

Residual Strength Characteristics of Polymer Fibre Concrete Exposed to Elevated Temperature

Abstract: Abstract. Mechanical properties of polymer based concrete exposed to high temperature effects are evaluated in the present study. Concrete mixtures were prepared using styrene butadiene rubber (SBR) latex and reinforced with polypropylene (PP) fibres. "Latex polymer modified concrete mixes consisting of different aggregate proportions, polymeric fibre contents (0.1 and 0.3% Vf) and fly ash contents (25 and 50%) were investigated for high temperature performance. Concrete specimens after required curing were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Certainly, cement is an essential material for the construction sector because of its many advantages including natural abundance, relatively low cost, appropriate mechanical properties, and etc. [2][3][4]. The primary raw materials for cement producing include limestone, shale, and clay, which are accounted over 90% by weight [5].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, cement is an essential material for the construction sector because of its many advantages including natural abundance, relatively low cost, appropriate mechanical properties, and etc. [2][3][4]. The primary raw materials for cement producing include limestone, shale, and clay, which are accounted over 90% by weight [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studying the extracted results, it was observed that there were no outliers but also a very poor fit due to a wide dispersion of the results. While the Thirumurugan 30 results were not classified as outliers during the linear regression for elastic modulus, the fact that they were excluded for compressive strength and their extremely high results for elastic modulus compared to the rest led to their exclusion when determining the proposed relationship. With those results included the R 2 = 0.417, whereas when they, as well as one low result from Rambo 41 (which becomes an outlier once the other results are removed), are excluded the adjusted R 2 increases to 0.888.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of the mix design parameters have a significant effect on the performance of concrete exposed to elevated temperature [8][9][10][11]. Several research studies have been carried out to improve the thermal stability of concrete exposed to elevated temperatures using various materials, such as fillers, nanoparticles, and fibers [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The length and weight fraction of BF are two interactive factors that influence on mechanical and fresh properties of cementitious composites. Khan and Cao [60] investigated the mechanical properties of basalt-fiber-reinforced cementitious composites with four different fiber lengths (3,6,12, and 20 mm) and also with a combination of various lengths and contents. The results indicated that the compressive strength of basalt-fiber-reinforced cementitious composites containing fiber with the length of 6 and 12 mm is higher than that with 3 and 20 mm length.…”
mentioning
confidence: 99%